2012
DOI: 10.1097/sap.0b013e31822592e7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Full-Thickness Scalp Resection for Management of Primary Scalp Melanoma

Abstract: BACKGROUND Scalp melanoma is aggressive and has a proclivity for regional metastasis. We hypothesize that subperiosteal scalp melanoma resection reduces in-transit/satellite recurrence, when compared to subgaleal resection. METHODS We identified patients with intermediate to deep, primary scalp melanoma referred to head/neck surgery over an eight-year period. Patients were compared based on scalp resection depth, including subperiosteal (resection to the level of calvarium) and subgaleal (resection including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…10,12,14,15,1720,2224,27,28,3034,3638,40 Percent take was >90% in studies not employing bone burring. 9,11,12,16,17,29,35,39,41 …”
Section: Resultsmentioning
confidence: 99%
“…10,12,14,15,1720,2224,27,28,3034,3638,40 Percent take was >90% in studies not employing bone burring. 9,11,12,16,17,29,35,39,41 …”
Section: Resultsmentioning
confidence: 99%
“…This method of excision also conveniently permits direct skin grafting to the periosteum and aside from several patients reported in this cohort, a sub‐galeal resection is our routine practice. The role of a deeper resection plane in the scalp has been raised as a potential reason for worse loco‐regional control after a WLE for scalp melanoma . The study by Pannucci et al, although limited in sample size ( n = 36), found a significantly worse rate of local metastases on univariate analysis for a sub‐galeal resection plane as compared with the sub‐periosteal plane for patients with primary scalp melanoma (26.3% vs. 0%; P = 0.047).…”
Section: Discussionmentioning
confidence: 99%
“…Most published series and registries integrate the outcomes of scalp melanoma with other anatomical sites, particularly the neck . To date, there are three analyses focusing on the patterns of recurrence for primary cutaneous scalp melanoma in the literature . Recent work by Pannucci and co‐workers suggested a potential advantage in local scalp control by performing a sub‐periosteal resection of the primary lesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One series demonstrated subperiosteal resection to decrease in-transit recurrence in node-negative primary scalp melanomas compared to subgaleal resection. 126 Melanomas overlying the parotid gland should be excised down to the parotid fascia; parotidectomy is indicated if melanoma involves the superficial parotid fascia.…”
Section: Treatmentmentioning
confidence: 99%